Research Universities: American Exceptionalism? - Rosovsky, Henry (International Higher Education, 2014)
Henry Rosovsky, Harvard's longtime Dean of the Faculty of Arts and Sciences, describes six key characteristics present in America's top tier of research universities: shared governance, academic freedom, merit selection, significant human contact, preservation of culture, and nonprofit status. Although often discussed individually, these six characteristics of quality are rarely discussed as a system and, contrary to a longstanding historical tradition, their presence does not preclude innovation and change. The author questions whether today's boards of trustees, the court of last resort in American higher education, are prepared to uphold the key characteristics of quality.